Ontological Security of Poland’s Resistance to the European Relocation and Resettlement Scheme - Divacitra, Anggita; Suharman, Yoga (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2024)
This article analyses Poland's foreign policy in resisting the European Union (EU) relocation and resettlement schemes from an ontological security perspective. The two aspects of ontological security theory utilized in this article, namely state biographical narratives and discursive strategies, and how these affect the changing pattern of Poland’s foreign policy behavior. The discourse analysis method was employed to interpret narratives developed in society and the ruling power. The results show that Poland's rejection is shaped through narratives propagated as an effort to defend the continuity of authenticity of Poland’s identity as a protector of traditional values, which are rooted in its socio-historical structures and collective memory of nations. Additionally, discursive strategies reveal that Poland has acted as a positive subject rather than an ‘other.’ The article aims to contribute to the development of ontological security studies related to how non-material factors underpin foreign policy behavior.